The effectiveness of gotu kola leaves (centella asiatica (l.) urban) extract with 1%, 2.5% and 5% concentrations as a mouthwash on streptococcus mutans bacteria in vitro - Ahyar Riza; Afifah F. Siregar (Journal of Dentomaxillofacial Science, 2021)
Objective: To determine the effectiveness of gotu kola leaf extract (Centella asiatica (L.) Urban) with a concentration of 1%, 2.5% and 5% as a mouthwash against the growth of Streptococcus mutans bacteria.Materials and Methods: This was a laboratory experimental study with a post-test only control group design. The research sample was Streptococcus mutans bacteria which was bred and cultured in the Microbiology Laboratory of the Universitas Sumatera Utara Hospital. The gotu kola leaves used in the study were extracted and made in the form of mouthwash at the Traditional Medicine Laboratory, Faculty of Pharmacy, Universitas Sumatera Utara. This study used five treatment groups, namely gotu kola leaf extract mouthwash with a concentration of 1%, 2.5%, 5%, Chlorhexidine Gluconate 0.2% (positive control), and DMSO (negative control). The test for five treatment groups was repeated 5 times with Kirby-bauer diffusion method.Results: The results showed that the mouthwash of gotu kola leaf extract (Centella asiatica (L.) Urban) can inhibit the growth of Streptococcus mutans bacteria by forming a clear zone on disc paper. The results were statistically analyzed using Kruskal-wallis and Mann-Whitney Test showed a significant difference in the diameter of the inhibition zone formed in each treatment group (p <0.005).Conclusion: There is effectiveness of gotu kola leaf extract with a concentration of 1%, 2.5% and 5% as a mouthwash in inhibiting the growth of Streptococcus mutans and the most effective concentration was 5%.